2005
DOI: 10.1111/j.1742-7843.2005.pto960324.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution – Bioequivalence Non‐Correlations

Abstract: The World Health Organization (WHO) rules (1996) recommend in chapter 3 ''Technical data for regulatory assessment'' that information for marketing authorization should contain among others in-documentation, equivalence data (comparative bioavailability, pharmacodynamic or clinical studies), and comparative in vitro dissolution tests. European rules concerning evaluation of bioavailability and bioequivalence (CPMP/EWP/QWP/1401/98) specify in chapter 5.2: ''Dissolution studies are always necessary and conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…These differences were observed by analyzing the mechanism of drug diffusion through the colloidal matrix, as well as the aqueous solution, and they were also affected by the interaction between the external surface of colloidal formulations and the internal compartment of colloidal carriers [32]. Our research group has previously demonstrated that a square root equation similar to Higuchi’s could be obtained by transforming the initial and the boundary conditions in solving Fick’s second law of diffusion [26]. Recent data also showed that this model could be widely used to investigate the release kinetics of dextran microspheres [33], poloxamer gels [34], and cylinder matrix systems [35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences were observed by analyzing the mechanism of drug diffusion through the colloidal matrix, as well as the aqueous solution, and they were also affected by the interaction between the external surface of colloidal formulations and the internal compartment of colloidal carriers [32]. Our research group has previously demonstrated that a square root equation similar to Higuchi’s could be obtained by transforming the initial and the boundary conditions in solving Fick’s second law of diffusion [26]. Recent data also showed that this model could be widely used to investigate the release kinetics of dextran microspheres [33], poloxamer gels [34], and cylinder matrix systems [35].…”
Section: Resultsmentioning
confidence: 99%
“…A similar square root law to the Higuchi equation was further used to describe the release kinetic of drugs from pharmaceutical formulations, which can be considered as an infinite reservoir at the interface with a large or semi-infinite solution [26,27,28]. The concentration of drugs inside solution can be expressed, using the following equation:cfalse(y,tfalse)=csfalse(1erf(y4Dt)false), where, y is the distance from the interface and erf ( z ) is the error function calculated as the area under the curve 2πex2, with the limit between 0 and z :erffalse(zfalse)=true0z2πex2dx,…”
Section: Methodsmentioning
confidence: 99%
“…In the fed conditions study appeared in addition an outlier subject, additionaly increasing the variability. However, in bioequivalence studies despite proposals, it is not yet permitted to discard outliers [26] .…”
Section: Results and Discussion Total Food Effect On Pharmacokineticmentioning
confidence: 99%
“…A similar square root law to Higuchi equation was further used to describe the release kinetic of drugs from pharmaceutical formulations, which can be considered as an infinite reservoir at the interface with large or semi-infinite solution [27][28][29]. The concentration of drugs inside solution can be expressed using the following equation:…”
Section: Other Square Root Lawsmentioning
confidence: 99%